Investigation of variations in microbial diversity in anaerobic reactors treating landfill leachate - (:unkn) unknown (I W A PUBLISHING, 2003)
A young landfill leachate containing elevated total ammonia concentrations frequently as high as 2,700 mg/l was anaerobically treated for 1,015 days in two different laboratory-scale anaerobic reactors configured as sludge blanket and hybrid bed. In this paper, the last 265 days of this long-term anaerobic treatability study are presented. Effects of high ammonia concentrations on reactor performances were correlated to the variations in microbial diversity by identifying the dominant microorganisms with FISH (fluorescent in-situ hybridization), cloning, DGGE (denaturing gradient gel electrophoresis) and morphological analysis. The results have indicated that the high ammonia landfill leachate can be treated successfully by using either an UASB or a hybrid bed reactor if temporary pH adjustments in the reactor influents are made when high ammonia concentrations are experienced. Consequently, COD removal efficiency is independent of microbial diversity and reactor configuration and it depends on the biodegradable portion of the leachate. Under this circumstance, stability of the reactors with low levels of acetate was supported by the abundance of Methanosaeta population. In both of the reactors, some populations of Methanobacteriaceae were also detected while other methanogenic species were virtually absent. However, after the termination of pH adjustment at Day 860, reactors immediately became unstable due to the sudden increase in free ammonia concentration up to 400 mg/l. COD removal efficiency decreased to 42% in the hybrid bed and to 48% in the UASB reactor. The durations of inhibitions were not long enough to severely deteriorate the massive Methanosaeta cells; therefore, many of them were again identified after two free ammonia inhibitions. However, subsequently, long filamentous morphologies of Methanosaeta cells shifted,to shorter filaments and they lost their aggregating property.
Keywords: cloning; DGGE; FISH; free ammonia; landfill leachate; methanogens; MUNICIPAL SOLID-WASTE; QUANTIFICATION; HYBRIDIZATION; BACTERIA; SLUDGE